The Learning Experiences of Foreign Language Students in A Culture Trip - Santoso, Martha Nandari (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2019)
This study examined the learning experiences of students of English as a Foreign Language in a culture trip that was conducted within the students' own multicultural society (Indonesia). The culture trip was aimed at providing the students with hands-on experience to learn about cross-cultural adjustment, skills to relate to people of other cultures, to be independent, and to act responsibly. Those skills are parts of the skills that people need to perform in the 21 st century environments. The study was guided by a research question: what were the students' learning experiences during the culture trip? The qualitative data for answering the research question were collected from the students' individual written reports of the trip, and the results of open-ended questionnaires given after the trip. The findings showed that for many of the students, the trip was their first independent travel experience which provided not only cross-cultural adjustment learning experience but also learning lessons about many of the skills needed in the 21 st century such as communication, using information technology, being self-directed, independent and responsible, managing goals and time, collaboration and working in a team. The study may be useful for teachers of language who would like to provide cross-cultural experiences and soft skills to the students to function effectively in 21st-century environments.